Seizure-induced overexpression of NPY induces epileptic tolerance in a mouse model of spontaneous recurrent seizures - Drexel, Meinrad; Sperk, Günther (Frontiers in Molecular Neuroscience, 2022)
Epileptic seizures result in pronounced over-expression of neuropeptide Y (NPY), and NPY exerts potent anticonvulsive actions through presynaptic Y2 receptors by suppressing glutamate release from principal neurons. We investigated whether seizure-induced over-expression of NPY contributes to epileptic tolerance induced by preceding seizures. We used a previously established animal model based on selective inhibition of GABA release from parvalbumin-containing basket cells in the subiculum/sector CA1. The mice present spontaneous recurrent seizures (SRS) and clusters of interictal spikes (IS). The frequency of SRS declines after five to six weeks indicating development of tolerance. NPY overexpression in interneurons, however, persists in spite of decreasing SRS frequency. A low dose of pentylenetetrazol induced minute EEG changes but presumably induced release of NPY. Concomitant treatment with the Y2 receptor antagonist JNJ 5207787 blocked the anticonvulsive action NPY and resulted in severe seizures. JNJ 5207787 alone did not induce convulsions. The data indicate that NPY overexpressed by SRS exerts a protective function. Only after stimulating NPY release by a low dose of PTZ, the Y2 receptor antagonist JNJ 5207787 antagonizes the protective action of NPY and precipitates severe seizures.